1988
DOI: 10.1029/gl015i002p00180
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of beryllium with H2O at high pressures: Implication for magma genesis in subduction zones

Abstract: The degree of transportation of beryllium with H2O is measured under the upper mantle P/T conditions in order to examine the incorporation of 10Be in subduction zone magmas. 5.4±0.3% of original beryllium in the starting serpentinite is extracted with H2O from the system through the dehydration reaction of serpentine at 850°C and 1.5 GPa. It follows that the partial melting of oceanic lithosphere including 10Be‐rich sediment layer is not necessarily required for inclusion of the isotope in island‐arc lavas. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Fiorentini and Beresford, 2008), or that Li within clinopyroxene and olivine are in disequilibrium (Seitz and Woodland, 2000). For Be, this is in-line with the experimental data of Tatsumi and Isoyama (1988) at 1.5 GPa and 850°C, where peridotite loses up to 5% of the initial Be mass. Such an extraction process potentially increases the Be concentration within the mantle wedge.…”
Section: Oceanic or Subcontinental Mantle?supporting
confidence: 84%
See 3 more Smart Citations
“…Fiorentini and Beresford, 2008), or that Li within clinopyroxene and olivine are in disequilibrium (Seitz and Woodland, 2000). For Be, this is in-line with the experimental data of Tatsumi and Isoyama (1988) at 1.5 GPa and 850°C, where peridotite loses up to 5% of the initial Be mass. Such an extraction process potentially increases the Be concentration within the mantle wedge.…”
Section: Oceanic or Subcontinental Mantle?supporting
confidence: 84%
“…Bebout et al, 1993;Ryan et al, 1996;Bouvier et al, 2008). However, Be shows some mobile behaviour under high T and P (850°C and 1.5 GPa) as suggested by Tatsumi and Isoyama (1988). They showed that a max.…”
Section: Oceanic or Subcontinental Mantle?mentioning
confidence: 66%
See 2 more Smart Citations
“…Solid-fluid parition coefficients for beryllium are consistently at least two orders of magnitude larger than partition coefficients for boron at 900°C and 2.0 GPa (Brenan et aI., 1998b). Experiments on serpentinite at 850°C and 1.5 GPa showed that only small amounts of beryllum were liberated with H20 during dehydration (Tatsumi and Isoyama, 1988).…”
Section: Lobe Mobilty In Fluidsmentioning
confidence: 99%